Impact of Environmental Factors on Student’s Educational Background and Their Future Performance - Muzamil Hussain AL Hussaini; Tariq Hussain (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study examine the impact of environmental factors on student’s educational background and their future performance among 500 male and female students of high school classes four tehsils of district Bhakkar. Environmental factors have both type of impacts positive and negative impacts on students educational development and their future development such as physical, moral, Socioeconomic status , Parental involvement and Peer influences .In this study objectives were to investigate (1).Identifying strategies to create a conducive learning environment (3) Developing interventions to mitigate negative environmental impacts (4) Raising awareness about the importance of environmental factors in education hypotheses and research questions were designed for the purpose of testing and answering through the collected empirical data from the sample group and these objectives testified by hypotheses. The population of the study included all the govt high school from which the researcher selected 500 respondents through stratified random sampling techniques. The design selected for the study was survey. The researcher designed research instruments for data collection from the respondents of the study, one was a Likert scale questionnaire